On Social Justice, Diversity, and Development: The Asian Context - Dy, Manuel B, Jr (Archīum Ateneo, 2019)
Introducing the main articles in this issue of Social Transformations, the overarching theme of social justice is explored in tandem with Amartya Sen’s concept of development as freedom. The main articles provide different ways of understanding social justice as economic justice, as based on human rights, and that which thrives on democracy. As Dr. Eduardo Araral presents in “The Asian Dilemma,” social justice in Asia continues to be an issue to this day precisely because the same drivers of progress are also the impetus of issues that plague Asian societies. Justin Joseph G. Badion tackles the global food crisis and uniquely provides an avenue for the Catholic Church to enter this discussion. Separately tackling the refugee crisis, Yamamoto Nobuto and Mon Mon Myat analyze the Rohingya and the Indochinese refugee crises emphasizing rights as the basis of social justice. Taniguchi Miyoko and the pair, Liang Guanghan and Xie Xiaowen, point to the importance of democracy (formal and material) for social justice to thrive through their articles on peacebuilding in Mindanao and gender equality in China, respectively. Through these articles, Sen’s perspective provides a key lens to tackle social justice in Asia from an Asian perspective but also concludes with the problems that arise from this perspective: prioritization of substantive freedom over instrumental freedom in situations of urgency, the conflict between legal rights and human rights in Asian societies with diverse cultures, and the emphasis on individual freedom over family identity.